One Year Outcomes of the H-AMIC Procedure for Osteochondral Lesions of the Talus - Anil Haldar MBBS BSc(Hons) FRCS PGCert; Amir Hossain Gahanbani Ardakani BSc (Hons), MBBS; Shelain Patel FRCS(Orth); Matthew J. Welck MD. MSc. BSc; Karan Malhotra MBChB (Hons), MRCS, FRCS (Tr&Orth); Nicholas Cullen MBBs, BSc, FRCS(Tr&Orth) (Foot & Ankle Orthopaedics, 2023)
Category: Ankle; Basic Sciences/Biologics Introduction/Purpose: Osteochondral lesions of the talus (OLTs) present a challenging clinical problem. Hyaluronic acid assisted autologous membrane-induced chondrogenesis (H-AMIC) is a technique where a polyglycolic acid and hyaluronin membrane scaffold (Chondrotissue ® ) is affixed over an area of talar bone marrow stimulation. Our study aims to assess the efficacy of this technique. Methods: We undertook a prospective study on consecutive adult patients at our unit who had H-AMIC procedures between January 2020 and November 2021 to treat single, symptomatic OLTs, >1.5cm 2 , refractory to previous management. Data was collected on patient reported outcomes (MOxFQ, EQ5D, satisfaction), ankle range of movement, and complications at 1-year post-surgery. Fifteen patients were included in this study with a mean age of 33.8±20.9 years. Mean duration of symptoms was 7.9±5.2 years, with a mean of 1.5 previous procedures (range 0 to 3). All patients had osteotomies to gain access to the OLT (13 medial malleolar, 2 fibular). Results: Mean improvements greater than the minimum clinically important difference (MCID) were seen in MOxFQ-Pain (61.7±26.1 to 48.3±21.8, p=0.112), MOxFQ-Walking (64.6±21.8 to 46.6±23.9, p=0.067), MOxFQ-Social (63.67±22.5 to 41.8±29.2, p=0.055), although none reached statistical significance. No difference was seen in EQ5D. Overall improvements were seen in MOxFQ-Pain in 58.3%, MOxFQ-Walking in 75%, and MOxFQ-Social in 83.3% of patients. Overall, 11 patients (73.3%) were satisfied with the procedure. Patients displayed improvement in plantarflexion from 33.1±5.5 to 42.0±7.9 degrees (p=0.002) and no change to dorsiflexion. There were no complications. Conclusion: The H-AMIC procedure is a promising and safe option for larger osteochondral lesions of the talus. Early results suggest improved range of motion despite osteotomy and clinically (but not statistically) significant improvement in function in a group of patients with longstanding symptoms and previous failed surgery. Larger, adequately powered cohorts may establish statistical efficacy of this technique compared with alternative techniques.